Uma câmera na mão e uma insegurança na cabeça: a relação de jovens adultos com as experiências laborais no Audiovisual - Justino, Jeniffer Cristina Ferreira (Universidade Federal de São Carlos, 2018)
The present research aimed to understand the relationship of young adults with work in the audiovisual field. For that, 5 young women and 5 young men, aged between 20 and 29 years, were interviewed about their experiences, challenges and expectations that permeate their insertion and permanence in the audiovisual labor sector. Despite the back and forth in search of work and/or professional qualification, the trajectories are somehow located in the city of Sorocaba, in the interior of São Paulo. However, some people came from the city of Sorocaba and went out looking for work/training and remain outside of the city; while other ones came from other cities to live/work in Sorocaba; and there even others that are from the city of Sorocaba, went out looking for work/training and returned to the city due to difficulties and/or other specific reasons. Nevertheless, in general, research is based on the relationship between Youth, Work and Audiovisual, and aimed to understand the relationships between experiences, expectations and challenges present in these work paths, as well as the different meanings of audiovisual in the life of each one, that being said, the research was based on four main questions: Who are these young people? What are your experiences? What challenges have they faced/face? What are your expectations? Thus, the present dissertation is the materialization of the effort and attempt to understand these trajectories/relations, and tries to answer them through the approximations between the theoretical contributions of Youth, Work and Audiovisual. Finally, having in mind the set of expectations and challenges that these young people face in the work environment and the relationships established with the family, training and with the work itself, we sought to understand the similarities, ambiguities and differences of these narratives and these paths.
A camera at hand and an insecurity in the head: the relationship of young adults with labor experiences in Audiovisual
Keywords: Juventude; Trabalho; Audiovisual; Youth; Job; Audiovisual; CIENCIAS HUMANAS; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS